The mixed effects of making contribution behaviors observable - Noel Z. Hoven; Karine Nyborg (University of Oslo, Department of Economics, 2025)
Voluntary contributions to public goods have been shown to increase when contribution behaviors become observable by peers. We examine the effect of social pressure on moral behaviour, using a framework distinguishing explicitly between observable and nonobservable forms of contribution. We show that even with moral motivation and social pressure, there is underprovision of the public good. Making some contribution behaviors observable does increase effort, but also causes misallocation of effort between observable and non-observable effort types. The latter negative effect can possibly outweigh the positive effect of increased effort on public good provision.
Keywords: 330; Moral motivation; Behavioural economics; Warm glow; Modeling visible altruism